Simple dynamic load balancing mechanism for structured P2P network and its evaluation. (1st January 2012) - Takeda, Atsushi; Oide, Takuma; Takahashi, Akiko
Many proposals have been advanced for structured Peer-to-peer (P2P) networks, but it is difficult for existing structured P2P networks to achieve dynamic load balancing sufficiently. In this paper, we propose a new structured P2P network called Well-distribution Algorithm for an Overlay Network (Waon), which achieves dynamic load balancing among nodes. Waon uses a simple algorithm of load balancing and a routing table-based on the number of hops between nodes to distribute a communication load uniformly. The proposed scheme enables object deployment-based on object semantics. Consequently, Waon can support range queries. Furthermore, the proposed scheme enables node deployment-based on node locality. Therefore, Waon can reduce the communication load on the physical network. Using simulation results, this report describes that Waon achieves dynamic load balancing sufficiently. Furthermore, simulation results in this paper demonstrate that Waon can reduce the load on the physical network.